2012
DOI: 10.5171/2012.798113
|View full text |Cite
|
Sign up to set email alerts
|

A Review of E-Financial Reporting Research

Abstract: Internet is a very exciting medium to look into especially with regards to presentation, disclosure and financial reporting. The Internet also has become one of users' most frequently used sources of information. Consistent with the innovation of the Internet as a cheap but powerful communication device, disclosure of financial and non-financial information on the Internet is becoming an increasingly popular subject of research. Internet reporting or e-reporting is a very powerful and useful tool for financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
10
0
8
Order By: Relevance
“…There are lots of studies conducted on internet as a medium of information/data distribution (Norris, 2001; Buhalis and Law, 2008;Xiang et al, 2015). Khan and Ismail (2012) concluded that web based reporting is cheap, easier and good investment decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are lots of studies conducted on internet as a medium of information/data distribution (Norris, 2001; Buhalis and Law, 2008;Xiang et al, 2015). Khan and Ismail (2012) concluded that web based reporting is cheap, easier and good investment decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous analyses by other researchers, two alternative ways of studying online accessibility become evident. Most of the studies analyze what factors influence online accessibility (Azli and Azizi, 2012), but a few studies focus on its impact on the organization (Gandía, 2008, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the absence of regulations made the web-based reporting voluntary and based mainly on the management policy of a company (e.g., Marston, 2003;Japan Sriram & Laksmana, 2006;Bui & Sankaran, 2009;Sánchez et al, 2011). This, however, affected the prior studies in online disclosure as most of them were descriptive in nature (e.g., Marston, 2003;Trabelsi et al, 2004;Khan & Ismail, 2011;Khan et al, 2013) with mixed results for those that investigated the determinants of such disclosure. Fourth,…”
Section: Final Remarks On Prior Literaturementioning
confidence: 99%